A new Journal for telecommunications with an added purpose - Gerrand, Peter (Journal of Telecommunications and the Digital Economy, 2019)
The Australian Journal of Telecommunications and the Digital Economy (ajTDE) is the reincarnation of the Telecommunications Journal of Australia (TJA), under the guidance of essentially the same Editorial Board – give and take a few distinguished members – who had moved the traditional ‘print and post’ version of TJA (published since June 1935) to its exclusively online version (from November 2007 to June 2013).